O fluxo de informação dos processos de consulta tributária da Receita Federal do Brasil: análise baseada no modelo australiano Records Continuum - Gama, Juliano Rezende (2021)
The research aims to analyze the implications of the guidelines and access to information and public transparency, brought by Law nº 12.527 / 2011, in the information flow of the tax consultation process of the Secretariat of the Federal Revenue of Brazil, regulated by Normative Instruction RFB nº 1.396/ 2013. For that, we used as hypothesis the application of the Records Continuum model as a guiding resource for understanding that its use by the Public Administration can be a way to meet the wishes of the Access to Information Law, because the principles that guide this model aim not to enclose the records and documents. This is an exploratory research with a qualitative approach that uses bibliographic and documentary research of an applied nature. It was explained about information flow in the context of information management and document management. More specifically, the information flow of the tax consultation was mapped and studied, which begins with the request of the consulting taxpayer and ends with the publication of the consultation solution by the Federal Revenue Service. This study also included data analysis in three stages: initially, an attempt was made to understand the axes and coordinates of the Records Continuum model applied to the tax consultation process. Then, this instrument of Tax Law was analyzed by the characteristics of the legal dimensions of the Records Continuum model. Finally, the information presented by the Federal Revenue was analyzed from the perspective of the Access to Information Law guidelines. The results showed improvements in line with the application of the guidelines of this Law in the informational environment assessed by the Federal Revenue, as the improvement in the mechanisms of access to information and transparency in the consultation solutions was identified and evidenced the Records Continuum model as capable of assisting the analysis of the flow of tax information by the Federal Revenue of Brazil to fulfill its mission of promoting tax justice for the benefit of society.